1999
DOI: 10.1017/s0029665199000968
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and immune function: effect of ageing and nutrition

Abstract: fax +45 3545 6648, email bkp@rh.dk Strenuous exercise is followed by lymphopenia, neutrophilia, impaired natural immunity, decreased lymphocyte proliferative responses to mitogens, a low level of secretory immunoglobulin A in saliva, but high circulating levels of pro-and anti-inflammatory cytokines. These exercise-induced immune changes may provide the physiological basis of altered resistance to infections. The mechanisms underlying exercise-induced immune changes are multifactorial and include neuroendocrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 105 publications
1
6
0
Order By: Relevance
“…A recent study showed that 24 h of continuous ultramarathon activity resulted in a higher level of LPS and increased levels of circulating pro-inflammatory cytokines [ 146 ]. In fact, prolonged intense physical exercise leads to elevated concentrations of counter-regulatory hormones in plasma such as cortisol and catecholamines related to low immunity [ 147 ]. In addition, high levels of muscle oxidative stress lead to an excessive production of ROS and inflammation [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…A recent study showed that 24 h of continuous ultramarathon activity resulted in a higher level of LPS and increased levels of circulating pro-inflammatory cytokines [ 146 ]. In fact, prolonged intense physical exercise leads to elevated concentrations of counter-regulatory hormones in plasma such as cortisol and catecholamines related to low immunity [ 147 ]. In addition, high levels of muscle oxidative stress lead to an excessive production of ROS and inflammation [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Also, gene polymorphisms ( 32 ) and biological markers ( 33 , 34 ) are suggested to be predictors of prognosis in patients with RCC. Although NLR is easy to measure, conditions such as active infection, inflammatory diseases, smoking behavior or stress at the time of blood collection may affect it ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…One caveat to consider is that although the NLR is easy to measure, the specificity of this parameter is influenced by several other conditions such as active infection, inflammatory diseases, smoking behaviour or stress at the time of blood collection (Pedersen et al , 1999; Alkhouri et al , 2012). In our opinion, these factors impair the use and generalisability of this marker as a specific predictor of survival in patient cohorts.…”
Section: Discussionmentioning
confidence: 99%